THE EFFECT OF ANTENATAL CARE SERVICE QUALITY AND THERAPEUTIC COMMUNICATION OF MIDWIFE ON MOTIVATION OF PATIENTS TO GIVE BIRTH AT MIDWIFE AND SPA HOUSE MRS. "F" IN JOMBANG DISTRICT - Mutiarasari, Farra Dibba; Ema Mayasari; Erma Retnaningtyas (Indonesian Journal of Nutritional Epidemiology and Reproductive, 2019)
The quality of antenatal care services can be told good is not only measured by the luxury of facilities, the completeness of technology but also communication of health workers or midwives must reflect professionalism and have high commitment, so that patients can provide a sense of satisfaction, trust, and patient loyalty. The purpose of this research was to determine the effect of antenatal care service quality and therapeutic communication of midwife on motivation of patients to give birth at Midwife and Spa House Mrs. "F" in Jombang district. This research is a quantitative research with analytical survey method with a cross sectional approach. The study population were 127 pregnant women. The samples were 86 pregnant women who visited at Midwife and Spa House Mrs. "F". The sampling technique uses accidental sampling. The independent variables in this study were antenatal care quality services and therapeutic communication midwives. The dependent variable in this study was patient’s motivation for maternity. Data were collected by questionnaires and tested by multiple linear regression tests. The results of the study showed that from 86 respondents, most of the respondents stated that the quality of antenatal care services was good, namely 58 respondents (67.4%). Therapeutic communication of midwife shows that the majority of respondents stated that therapeutic communication of midwife was good, namely 61 respondents (70.9%). Motivation of patient shows that the majority of respondents had a strong motivation for give birth which was 65 respondents (75.6%). There is a effect of antenatal care service quality and therapeutic communication of midwife on motivation of patients to give birth at Midwife and Spa House Mrs. "F" in Jombang district. It is expected to submit input, criticism and suggestions related to the quality of antenatal care services, therapeutic communication of midwives in motivating patients to give birth, so that improvements can be made